An Efficient Securing Data using Enhanced Key Policy Attribute based Encryption in Cloud - Saraswathi, M.; Bhuvaneswari, T. (International Journal of Engineering and Technology, 2018)
With the tremendous growth of sensitive records on cloud, cloud security is getting more necessary than even before. The cloud data and offerings reside in hugely scalable statistics centers and can be accessed everywhere. The increase of the cloud customers beenÂ Â Â Â Â Â Â Â Â Â accompanied with a growth in malicious undertaking in the cloud. More and more vulnerabilities are discovered, and nearly every day new security advisories are published .In this regard to protect data from leaking, users need to encrypt the data before outsourcing. The Cloud service provider (CSP) should ensure integrity, availability, privacy and confidentiality of user data. The objective of this paper aims to provide a solution that ensures the storage of data securely in the cloud. A Proposed an algorithm as enhanced-key policy attribute-based encryption scheme (KP-ABE) for data security in cloud storage .Data owners encrypt their secret data for the dataÂ Â Â Â Â Â receivers using enhanced KP-ABE algorithm. By applying proposed algorithm overall key generation, Encryption and decryption time is minimized.Â Â